(untitled) (Experimental biology, 2021)
Due to the increased Toxicological and environmental hazards of pesticides, the decrease in demand for them due to their lack of efficiency, low stability during storage, and violation of the integrity of packaging, the problem of accumulation of prohibited, unusable pesticides in the former territories of storage facilities for chemical plant protection products is acute in the Republic. The study of the composition of microbiocenoses of contaminated soils, as from the territory of disposal of toxic chemicals, is of significant scientific interest both for monitoring the environment and for isolating microorganisms that are resistant to high doses of toxicants. The method of cleaning soils contaminated with pesticides, using microorganisms-biodestructors, is undoubtedly effective and economical. In this work, we studied the microbial diversity of soil in the territories adjacent to the places where pesticides are buried. Samples of soil samples were taken from 7 points (kyzylkairat village, Beskaynar village, Amangeldy village-Brigade 1 (warehouse 1 and warehouse 2), Belbulak village, Brigade 2-Almaty Plemzavod JSC, Taukaraturzh village (control) of Talgar district of Almaty region. The characteristic of microbial and fungal flora in selected soil samples from locations of obsolete pesticides is given. 40 strains of pure cultures of microorganisms were isolated, morphological and cultural, physiological and biochemical properties were studied. As a result of studying morphological - cultural and physiological - biochemical properties, the selected cultures were previously assigned to the genera Bacillus, Rhodococcus, Pseudomonas, Rhodotorula. Key words: pesticides, microorganisms-destructors, degradation.